MOTIVASI PETANI DAN TINGKAT ADOPSI TEKNOLOGI TERHADAP PENDAPATAN USAHATANI KACANG TANAH PADA PERTANIAN LAHAN KERING - Yohanes G. Bulu; Ika Novita Sari; Sylvia Kusumaputri Utami (JURNAL AGRICA, 2020)
The motivation of farmers in adopting groundnut cultivation technology, especially relay cropping patterns technology of corn and groundnut on dry land is relatively low. The study aims to determine the motivation of farmers in adopting groundnut cultivation technology that can increase farmers' incomes. The study was conducted in Labangka Subdistrict, Sumbawa Regency from December 2016 until August 2017 using survey approach. Data collection techniques carried out by observation, recording, and in-depth interviews with respondents. The sample population who adopted corn relay cropping pattern with groundnuts was 276 people. Determination of the sample of respondents was purposive as many as 40 people. Data were analyzed using descriptive analysis method. The results showed that the motivation of farmers in adopting technology was 79,29%. The adoption rate of groundnut technology components was 81,39%. Net income level or profitability of groundnut farming produced in the rainy season averages Rp 9.967.500/ha with an R/C Ratio of 2,65. Net income level or profitability of groundnut farming cultivated in the dry season averages of Rp 8.517.000/ha with an R/C ratio of 3,34. The R/C ratio value is more than 1 on groundnut farming that are cultivated in rainy season or in dry season are feasible to be cultivated because it can provide benefits and high income.